2012
DOI: 10.1136/gutjnl-2012-304038
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol for primary prophylaxis of variceal bleeding in cirrhotic patients with haemodynamic non-response to propranolol

Abstract: Objective Non-selective β-blockers or endoscopic band ligation (EBL) are recommended for primary prophylaxis of variceal bleeding in patients with oesophageal varices. Additional α-adrenergic blockade (as by carvedilol) may increase the number of patients with haemodynamic response (reduction in hepatic venous pressure gradient (HVPG) of ≥20% or to values <12 mm Hg). Design Patients with oesophageal varices undergoing measurement of HVPG before and under propranolol treatment (80-160 mg/day) were included. HVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
239
0
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(276 citation statements)
references
References 28 publications
12
239
0
14
Order By: Relevance
“…Reiberger et al demonstrated that 56% patients who failed to achieve an adequate reduction in HVPG with propranolol achieved a response with Carvedilol, with remaining patients undergoing EVL. Patients receiving Carvedilol were found to have a significant reduction in bleeding rate, hepatic decompensation and death compared to patients receiving EVL [16]. Thus, Carvedilol (6.25 mg increasing to 12.5 mg oral daily) should be considered a first-line agent in the primary prophylaxis of AVB.…”
Section: Prophylaxis Of Variceal Bleedingmentioning
confidence: 99%
“…Reiberger et al demonstrated that 56% patients who failed to achieve an adequate reduction in HVPG with propranolol achieved a response with Carvedilol, with remaining patients undergoing EVL. Patients receiving Carvedilol were found to have a significant reduction in bleeding rate, hepatic decompensation and death compared to patients receiving EVL [16]. Thus, Carvedilol (6.25 mg increasing to 12.5 mg oral daily) should be considered a first-line agent in the primary prophylaxis of AVB.…”
Section: Prophylaxis Of Variceal Bleedingmentioning
confidence: 99%
“…karwedilolu jest nie tylko dobrze tolerowane, ale i bardziej efektywne w obniżaniu ciśnienia wrotnego niż kuracja propranololem (80-100 mg/d. ), przy podobnym wpływie na systemowe ciśnienie tętnicze i częstość rytmu serca; zwiększenie dawki karwedilolu nie przynosi większych korzyści, jednocześnie narażając chorych na wystąpie-nie niekorzystnych działań ubocznych, to jest hipotensji i bradykardii [22]. Wiadomo, że podanie nieselektywnych antagonistów receptorów beta-adrenergicznych może redukować ciśnienie wrotne poniżej 12 mm Hg i tym samym zmniejszać częstość występowania krwawienia z żylaków przełyku i gastropatii wrotnej, dodatkowo skraca wydłużony odstęp QT i redukuje objawy zespołu hiperdynamicznego u chorych z marskością wątroby oraz zmniejsza częstość występowania poważnego powikłania marskości wątroby, jakim jest spontaniczne bakteryjne zapalenie otrzewnej.…”
Section: Kliniczne Znaczenie Kardiomiopatii Wątrobowejunclassified
“…26 Although nonselective B-blockers (NSBB) such as nadolol or propranolol do not prevent the development of varices, they can effectively achieve primary and secondary variceal hemorrhage prophylaxis and are therefore the standard of care for prevention. 27 Some high MELD patients are candidates for NSBB; however, recent data have raised concerns about the risk of NSBB in patients with refractory ascites after SBP development, and those patients require banding to obliteration.…”
Section: Variceal Bleedingmentioning
confidence: 99%